2008
DOI: 10.2105/ajph.2006.102525
|View full text |Cite
|
Sign up to set email alerts
|

Approaching Health Disparities From a Population Perspective: The National Institutes of Health Centers for Population Health and Health Disparities

Abstract: Addressing health disparities has been a national challenge for decades. The National Institutes of Health-sponsored Centers for Population Health and Health Disparities are the first federal initiative to support transdisciplinary multilevel research on the determinants of health disparities. Their novel research approach combines population, clinical, and basic science to elucidate the complex determinants of health disparities. The centers are partnering with community-based, public, and quasi-public organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
396
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 460 publications
(417 citation statements)
references
References 38 publications
8
396
0
Order By: Relevance
“…Thus, housing reflects physical context of daily living which can potentially contribute to disparate health outcomes in the model for disparate health outcome suggested by Warnecke. 17 Yet, no systematic study of the use of housing data to construct a measure of individual SES has been reported. To address these concerns, we developed a housing-asset-based measure of SES (hereafter, HOUSES) and compare it to existing SES measures and health outcomes known to be associated with SES.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, housing reflects physical context of daily living which can potentially contribute to disparate health outcomes in the model for disparate health outcome suggested by Warnecke. 17 Yet, no systematic study of the use of housing data to construct a measure of individual SES has been reported. To address these concerns, we developed a housing-asset-based measure of SES (hereafter, HOUSES) and compare it to existing SES measures and health outcomes known to be associated with SES.…”
Section: Introductionmentioning
confidence: 99%
“…56 To fully address racial disparities, additional potential barriers at the health care system, community, and policy level also merit consideration. 57,58 Several limitations of our study should be noted. First, our method of ascertaining adherence excludes patients who obtained less than two dispensings of a medication; thus we are unable to identify non-adherent patients in cases where medications were prescribed but never dispensed or where a new medication was only dispensed a single time.…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, the Coordination Center fostered and facilitated the sharing of resources and expertise across sites. Secondly, because TREC was able to promote and support work across disciplines and site, in part through the Coordination Center, TREC did not experience the two to three-year lag in publications to the same degree as TTURC and CPHHD [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Population Health and Health Disparities (CPHHD) [2] TTURC was the first to undergo evaluation of its impact on research output, as measured by the timing of publications. A retrospectively-conducted bibliographic evaluation of TTURC in comparison with R01s found that after an initial two to three-year lag period, TTURC had higher overall publication rates over a 10-year comparison period [3].…”
Section: Nih Transdisciplinary Initiatives and Their Evaluationmentioning
confidence: 99%